Perimyocarditis as first sign of systemic onset juvenile idiopathic arthritis treated successfully with anakinra: a case-based review - Ciancia, Silvia; Cappella, Michela; De Fanti, Alessandro; Iughetti, Lorenzo (Acta Biomedica Atenei Parmensis, 2020)
Background: The involvement of myocardium and pericardium at the same time is very uncommon as first manifestation of juvenile idiopathic arthritis with systemic onset (soJIA). Case: A fourteen years-old boy, referred with symptoms of acute gastroenteritis, developed a perimyocarditis as first manifestation of Still’s Disease, after only one day from the admission. The rheumatologic disease was not responding to glucocorticoid treatment. The use of anakinra was the key point of the therapy and after its administration the patient started to recover fastly. Conclusions: This case report describes cardiac involvement as first sign of soJIA and the successful use of anakinra inducing remission of soJIA not-responding to steroid therapy.